2011
DOI: 10.1016/j.jnutbio.2009.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Emulsified lipids increase endotoxemia: possible role in early postprandial low-grade inflammation

Abstract: Low-grade inflammation is a risk factor for the onset of atherosclerosis. Little is known about the involvement of endotoxin absorption from the gut during the digestion of lipids. In the present study, we first investigated in humans the impact of a mixed meal containing dispersed lipids on postprandial endotoxemia and inflammation. We then investigated the effect of (i) oil emulsification in vivo in rats and (ii) fatty acid amounts in vitro using Caco-2 cells on postprandial endotoxemia. In humans, postprand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
196
4
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(218 citation statements)
references
References 47 publications
10
196
4
8
Order By: Relevance
“…This may contribute to chronic low-grade inflammation as manifested in chronic diseases such as diabetes, Parkinson disease, and atherosclerosis (2)(3)(4)(5)(6). Mechanistically, a super-low dose of endotoxin results in a mildly sustained activation of proinflammatory mediators without the activation of anti-inflammatory mediators, allowing low-grade, non-resolving inflammation to persist (7).…”
mentioning
confidence: 99%
“…This may contribute to chronic low-grade inflammation as manifested in chronic diseases such as diabetes, Parkinson disease, and atherosclerosis (2)(3)(4)(5)(6). Mechanistically, a super-low dose of endotoxin results in a mildly sustained activation of proinflammatory mediators without the activation of anti-inflammatory mediators, allowing low-grade, non-resolving inflammation to persist (7).…”
mentioning
confidence: 99%
“…In this study we have shown the importance of the dilution factor in human, mice, rat and pigs; and compared 4 different dilution factors in pigs to explain our rationale. The methodology used in our case to measure endotoxemia combined dilution, heat and sonication to increase the dispersion of LPS in the sample [4]. Moreover great care was taken to avoid contaminations during the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxins of the Gram-negative bacteria, when released into the intestinal lumen after cell lysis, have a high pyrogenic activity and can induce and maintain a low-grade inflammation [3,4]. For a long time the measurement of pyrogenic molecules has been a regulatory requirement for some pharmaceutical supplies including injectables, medical and surgical equipment and dialysis samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations